1997
DOI: 10.1002/anie.199710921
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Alkyl(dicarbonyl)(chloro)‐ruthenium Dimers in the Ruthenium‐Catalyzed Addition of Alkyl Formates to Ethylene

Abstract: COMMUNICATIONS treated with 2.2 equivalents of 4 (prepared from l-triisopropyl-siIylo~y-3,3-diiodopropane~~~~ and Et,Zn) and 1 equivalent of 3 (Scheme 3). Furthermore, the diastereo-and enantioselectivity for these processes were excellent. [20] In summary, we have developed an expedient and efficient synthesis of enantiomerically enriched 1,2,3-substituted cyclopropanes from allylic alcohols. In addition, we have presented the first cyclopropanation reaction of a functionalized iodoalkylzinc reagent. Applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
3

Year Published

1999
1999
2001
2001

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 39 publications
1
20
0
3
Order By: Relevance
“…IR monitoring of the reaction shows that, after 2 min, the dark-red solution contains a carbonyl species at low concentration since a weak carbonyl band is detected at 2092 cm Ϫ1 . After 2 ] in 70% yield after recrystallization of the crude product from dichloromethane/n-heptane (see Table 1). …”
Section: Infrared Monitoring Of the Reduction And Identification Of Smentioning
confidence: 99%
See 2 more Smart Citations
“…IR monitoring of the reaction shows that, after 2 min, the dark-red solution contains a carbonyl species at low concentration since a weak carbonyl band is detected at 2092 cm Ϫ1 . After 2 ] in 70% yield after recrystallization of the crude product from dichloromethane/n-heptane (see Table 1). …”
Section: Infrared Monitoring Of the Reduction And Identification Of Smentioning
confidence: 99%
“…[1Ϫ17] Nevertheless, in some cases, its implication as a reactant has been observed and solvent effects that do not seem to be directly linked with its polarity have been noticed, particularly when the catalytic reaction involves carbon monoxide or further reactions with carbonyl compounds. Thus, in the course of an investigation of the ruthenium-catalyzed hydroesterification of ethylene, the results of which have been reported previously, [1,2] a strong solvent effect was noted. In this reaction, the solvent could be involved in the formation of the active species; in particular, the complex [PPN][RuCl 3 (CO) 2 (DMF)] has been isolated after reaction of the precatalyst [PPN][RuCl 3 (CO) 3 ] with boiling DMF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a long time, these complexes were mainly regarded as intermediates for the preparation of more elaboptimum activity. [60] It was shown that, under the reaction conditions, the alkyl moieties were derived principally from orate species.…”
Section: Ii1 Evolution Of Ru 3 (Co)mentioning
confidence: 99%
“…General scheme for the reaction of face-sharing bioctahedral species with nucleophiles 16e Ϫ -acyl species [Ru{C(O)R}(PR 3 ) 2 (CO)Cl] (Scheme 27). [60] If X is an alkenyl group, whether it migrates or not depends on the nature of the starting alkyne. As shown in Scheme 27 [82] It is noteworthy that the same appearing in the scheme denotes a vacant coordination site on the metal center complexes were originally prepared by Ros [83] from RuH(CO)Cl(PR 3 ) 2 .…”
Section: Ii34 a New Binary Carbonylchlororuthenium(ii) Speciesmentioning
confidence: 99%